Numerical study on novel airfoil fins for printed circuit heat exchanger using supercritical CO2. (June 2018) - Cui, Xinying; Guo, Jiangfeng; Huai, Xiulan; Cheng, Keyong; Zhang, Haiyang; Xiang, Mengru
Highlights: Two novel fins are proposed to optimize the airfoil fin PCHE. The proposed fins have better performance than the referred fin. Staggered arrangement and proper shape could improve thermal–hydraulic performance. The enhancement mechanism could be explained with field synergy principle. Abstract: The Printed Circuit Heat Exchanger (PCHE) has attracted a lot of attentions recently due to its high efficiency and compactness, and the airfoil fin has excellent thermal–hydraulic performance compared with the zigzag channel in PCHE. Two novel fins were proposed in this study based on the configuration of NACA 0020 airfoil fin, in order to further improve the performance of airfoil fin PCHE. The thermal–hydraulic performance and the enhancement mechanism of the fins were numerically investigated using supercritical CO2 as the working fluid. The results showed that one of the novel fins has better comprehensive performance and less entransy dissipation than the NACA 0020 airfoil fin used in PCHE, since the j factor of this novel fin is 2.97–6.15% larger, and the pressure drop is 0–4.07% less than the NACA 0020 airfoil fin under the selected conditions. And the staggered arrangement and the proper shape of fins could reduce the effect of boundary layer and improve the thermal–hydraulic performance effectively. In addition, the enhancement mechanism of the novel fin PCHE could be explained with field synergy principle very well.